2011
DOI: 10.4085/1062-6050-46.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eating Disorder Risk and Body Image Distortion Among National Collegiate Athletic Association Division I Varsity Equestrian Athletes

Abstract: Context: Participation in appearance-based sports, particularly at the collegiate level, may place additional pressures on female athletes to be thin, which may increase the likelihood of their resorting to drastic weight control measures, such as disordered eating behaviors.Objectives: (1) To estimate the prevalence and sources of eating disorder risk classification by academic status (freshman, sophomore, junior, or senior) and riding discipline (English and Western), (2) to examine riding style and academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
6
25
1
2
Order By: Relevance
“…Body image dissatisfaction has been identified as a relevant factor in the development of disordered eating behaviors in athletes of both sexes. 4,5,26,27 Our results indicate that 14.7% of athletes are dissatisfied with their body image, which is lower than the prevalence of athletes with disordered eating behaviors (27.6%). Pritchard et al found a higher prevalence of disordered eating behaviors in athletes compared with non-athletes, but no difference in body image dissatisfaction between both groups.…”
Section: Figure 1 Association Between Disordered Eating Behaviors Andcontrasting
confidence: 42%
“…Body image dissatisfaction has been identified as a relevant factor in the development of disordered eating behaviors in athletes of both sexes. 4,5,26,27 Our results indicate that 14.7% of athletes are dissatisfied with their body image, which is lower than the prevalence of athletes with disordered eating behaviors (27.6%). Pritchard et al found a higher prevalence of disordered eating behaviors in athletes compared with non-athletes, but no difference in body image dissatisfaction between both groups.…”
Section: Figure 1 Association Between Disordered Eating Behaviors Andcontrasting
confidence: 42%
“…Interestingly, results are mixed as to which female athletes are more susceptible to eating disorders and disordered eating behaviors and whether athletes are at a higher risk compared with females in the general population. 7,[10][11][12][13] Estimates of these behaviors may differ widely because of factors such as sample size, competition level of athletes, type of sport, and social and cultural norms that may vary geographically. Therefore, the prevalence of eating disorders among various groups remains unclear.…”
mentioning
confidence: 99%
“…Sebagian besar memiliki persepsi tubuh negatif lalu perlahan menunjukkan gejala depresi, hal ini sangat berisiko untuk berkembang menjadi eating disorders. (16)(17)(18) Namun, berbeda dengan penelitian yang dilakukan oleh Kurniawan et al (11) di Bogor, bahwa tidak semua subjek yang memiliki persepsi tubuh negatif merasa cemas akan berat badan dan bentuk tubuh yang dimiliki saat ini, dan tidak memiliki dorongan atau keinginan untuk menurunkan berat badan sehingga tidak berisiko untuk berkembang menjadi eating disorders. (11) Tujuan penelitian ini adalah menganalisis hubungan antara persepsi tubuh dengan eating disorders pada remaja usia 15-19 tahun.…”
Section: Pendahuluanunclassified
“…Sebagian besar status gizi responden adalah normal. Hal ini sesuai dengan penelitian yang dilakukan oleh Torres-McGeehee et al (16) dan Watkins et al (21) bahwa pada sebagian besar subjek penelitian didapatkan kategori status gizi normal pada remaja dibanding dengan Eating disorders kategori status gizi yang lain. Pada penelitian ini didapatkan adanya hubungan yang bermakna antara status gizi dan persepsi tubuh.…”
Section: Pembahasanunclassified